OPTIMALISASI PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) MELALUI PROGRAM PENYULUHAN MASYARAKAT DI KELURAHAN SISIR, KOTA BATU, JAWA TIMUR - Novitasari, Dian; Jagad Al-Ayoubi, Sholahuddin; Nazzia, Saqinah; Mayshafajar K, Muhammad (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
Counseling is a process of disseminating information, playing a role in shaping attitudes, behaviors, and active involvement of the community in positive change and sustainable development, as well as so that people can live according to what they should be. Complete Systematic Land Registration (PTSL) is one of the initiatives of the Government of Indonesia in an effort to simplify and optimize the administrative process and land ownership in various regions. The geographical condition of Batu City, which continues to develop as one of the urban areas in East Java, has its own complexity in terms of land administration. The number of land disputes and the unclear status of ownership are serious challenges that affect the social and economic stability of local communities. This community service activity is carried out using the lecture and discussion method. In the first session, PTSL material was delivered. In the second session, a direct discussion session was held between the extension team and the community. Through direct interaction, the community has the opportunity to ask questions, share views, and express opinions or inputs related to the implementation of PTSL in Sisir Village. With the implementation of this activity, it is hoped that it will not only improve public understanding of the land registration process more efficiently, but also encourage public awareness of the importance of legal and registered land registration so as to avoid land disputes or conflicts.